Fundacje korporacyjne w Polsce - Gołaszewska-Kaczan, Urszula (Annales. Etyka w Życiu Gospodarczym, 2014)
Corporate foundations are structures created by companies to conduct socially responsible activities. They are intended to make these activities more profes-sional, better organised and coordinated. The foundations can also serve as a way of creating a positive image of a firm. The aim of the article is to present this form of business activity through illustrating the basic characteristics of corpo-rate foundations and the issues connected with operating them in Poland.